THE USE OF PAIN SCALE IN THE NEONATAL INTENSIVE CARE UNIT AND ITS BENEFITS IN THE APPLICABILITY OF NURSING CARE - Lucas Viana Roly, Damião; Gomes de Souza Silva, Lúcia; Brandão de Melo, Liliane; Allyson Gomes Ferreira, Jefferson; Carolina Salustino dos Santos, Maria; Claudino do Nascimento, Nathalia; da Silva Carvalho, Denise; Gnecco de Almeida, Adriana; Dayanna Alves Resende, Tamires (Health and Society, 2022)
Introduction: Pain is a symptom that is part of the premature newborns everyday in the Neonatal Intensive Care Unit due to the large number of painful procedures to which they are subjected during their stay. The nurse and the nursing staff because they are professionals responsible for the largest follow-up of neonates during their stay, play an important role in the careful observation and identification of the occurrence of signs that reflect the presence of pain. Objectives: To identify pain scales used in hospitalized newborns; evaluate the applicability of pain scales and benefits for nursing professionals. Methodology: It is an integrative review, which was carried out in search of the Virtual Health Library (BVS), in December 2017, using the keywords pain measurement, Intensive Care Unit and Neonatal Newborn. Results: Results were obtained with the number of publications in accordance with the theme. By analyzing the articles, the scales identified in the newborn pain in intensive care unit environment were NIPS, NFCS, CRIES, PIPP, COMFORT and others did not use scales. There was a predominance in the use of NIPS, since five of the nine selected articles opted for using this scale. The applicability of the pain and the benefits for nurses scales, it is necessary that professionals feel safe with the instrument used in its collection, really assessing pain systematically. The act of participating in training and updating of staff makes the nurse applied properly and uniformly to correct use of the scale. Conclusion: It is suggested that neonatal pain should be considered as the 5th sign of life, but the nurse has a fundamental role to evaluate this phenomenon through the pain assessment scales, providing comprehensive care to the newborn.